Strategi Komunikasi Badan Perencanaan Pembangunan Daerah Terhadap Perangkat Daerah Dalam Mengatasi Stunting di Kabupaten Ciamis - Nurfaidah, Hasna; Repa Nurlaela; Regi Refian Garis (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Stunting is a serious public health problem in Ciamis Regency. The Regional Development Planning Agency (Bappeda) has a key role in coordinating efforts to overcome stunting. This study aims to analyze the communication strategies used by Bappeda to interact with regional officials in order to overcome stunting. Research methods involve interviews, observation, and document analysis to understand communication practices and barriers faced by Bappeda. The results of data analysis show that communication between Bappeda and regional officials is a key factor in efforts to overcome stunting in Ciamis Regency. Effective communication strategies can improve coordination and collaboration between related parties.